Recurrence and mortality rate in an Italian multi-center case series of parathyroid atypical adenomas and carcinomas - Barale, Marco; Nervo, Alice; Craparo, Andrea; Pusterla, Alessia; Retta, Francesca; Maiorino, Federica; Castellano, Elena; Piovesan, Alessandro; Gianotti, Laura; Borretta, Giorgio; Procopio, Massimo; Arvat, Emanuela (Frontiers in Endocrinology, 2023)
Introduction. There are few data regarding the clinical outcome of patients with parathyroid atypical adenoma (AA) and carcinoma (PC) after surgery. Aim of our study was to investigate disease recurrence and mortality rate as well as their predictors in a series of patients with AA or PC. Methods. Clinical and biochemical parameters, histological features, incidence of disease recurrence and mortality rate were retrospectively assessed in 39 patients (51% males, mean age 56.2±17.2 years) diagnosed with PC (n=24) or AA (n=15) and followed up for 6.8±5.0 years after surgery. Results. No differences in baseline characteristics were registered between the two groups, except for higher KI67 values in PC than AA (6.9±3.9% vs 3.4±2.1%, p<0.01). Eight patients (21%) experienced recurrence after a mean follow-up of 5.1±2.7 years, with higher relapse rate in PC than AA (25% vs 13%), though this difference did not reach statistical significance. Mortality rate was 10% in the whole sample, without significant differences between AA and PC. Relapsing cases had been undergone the most extensive surgery more frequently and they had a higher mortality rate in comparison to non relapsing patients (38% vs 6% and 38% vs 3%, respectively, p<0.03 for both). In comparison to survivors, deceased patients were submitted to the most extensive surgery more frequently (50% vs 9%), they were older (74.8±4.6 vs 53.2±16.3 years), and they had higher KI67 values (11.7±4.9 vs 4.8±2.8, p<0.03 for all comparisons). Conclusions. During seven-year follow-up after surgery, no significant differences in recurrence and mortality rate were observed between PC and AA patients. Death was associated with disease relapse, older age and higher KI67 values. These findings suggest a similar and careful long-term follow-up in both parathyroid tumors, especially in older patients, and emphasize the need of further studies in large cohorts to throw light on this crucial clinical issue.